PENGEMBANGAN PERANGKAT PEMBELAJARAN PELUANG BERBASIS RECIPROCAL TEACHING UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI SMK NEGERI 3 LUBUKLINGGAU - Yulianti; Zulkardi; Putri, Ratu Ilma Indra (Mathematics Education Journal, 2010)
This research purposes to result valid and practical opportunity learning equipment on reciprocal teaching in class XI SMK, to observe the effect of teaching ware on reciprocal teaching towards mathematic critical thinking skill of SMK student. The subjects of the research were the 26 students of class XI TMR 3 SMKN 3 Lubuklinggau. Data collecting methods such as: Walk through, documentation, and critical thinking test. All collected data was descriptively and quantitatively analyzed. The analysis results concluded that the researcher had resulted the product of valid and practical opportunity learning ware on reciprocal teaching basis for students of class XI SMK. It has potential effect towards student’s mathematic critical thinking skill. Based on this result, it is suggested to develop and apply learning ware on reciprocal basis for other subjects. DOI: 10.22342/jpm.4.2.819